Mobile Navigation in Emergency Environment Using Wireless Sensor Networks - R.Rajasaranyakumari, Ms.; R.Karthikeyan, Mr; Bakyalakshmi, M; Geethanjali, R; Priyadharshini, K (International Journal of Engineering and Technology, 2018)
WSN's are used with the ultimate objective of condition checking and are a trademark choice of the system to enable emergency to course services. Even though The course routes picked by the present technique guarantee productive course and gives perfect most secure route by using the min-max rule close by the quantiï¬cation approaches ,however fails to identify the gathering .In the present structure we used an estimation called as SEND which does not revolve around the stop up at a particular zone however, in the proposed structure we use a computation called as CAN i.e blockage adaptable navigation, which bases on the congested locale by swarm recognizing and associates the person to move in an elective way where the hazard level is low and the A* figuring for briefest path. The proposed system moreover has the segment to show no less than two ways which improves the prosperity by empowering the customer to pick the most pleasing path .By coordinating customers following the dive edge of the hazard potential field , The CAN count can along these lines gain guaranteed ground of course and give perfect prosperity.Â Â